Applicability and benefits of the ecosystem concept in the construction industry. Issue 2 (1st February 2016) - Pulkka, Lauri; Ristimäki, Miro; Rajakallio, Karoliina; Junnila, Seppo
Abstract : Inter-firm collaboration has increased significantly in the last decades. The concept of ecosystem has emerged to explain the nature and implications of businesses' increasing reliance on networks. The ecosystem concept is intended to be generalizable across sectors, but research on ecosystems has focused on high-tech industries. Moreover, the construction industry has special features that differentiate it from other industries. In this paper, the concept of the ecosystem is introduced and developed in the context of the construction industry and the relationship between ecosystem characteristics and value creation in construction networks is examined. Based on a multiple-case study of six networks in the Finnish and Swedish construction industry, it is suggested that the ecosystem concept is applicable and offers a useful analytical lens for understanding value creation in the construction industry. The results suggest that operating according to ecosystem principles is positively connected to value creation in construction networks. Based on a cross-case analysis, a conceptual framework is presented on the main connections between ecosystem characteristics and value creation. The relevance of the ecosystem concept for the construction industry is predicted to grow in the future, as previous studies suggest that ecosystem-like features are being increasingly employed in construction networks.